IMAGE QUALITY ANALYSIS 4 CHAMBER SECTIONS OF CARDIAC MRI WITH AND WITHOUT UTILIZING SHIM VOLUME IN THE STEADY STATE FREE PRECESSION SEQUENCES - Wicaksono, Clinton Johan Ade; Suswaty, Susy; Apriantoro, Nursama Heru; Sasongko, Ary (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Cardiac MRI examination is relatively rare in Indonesia. The effect of the use of volume shim on moving organs, such as the heart is relatively unknown and noticed by radiographers and cardiologists. Purpose: To analyse the image quality of 4 chamber sections of Cardiac Magnetic Resonance Imaging with and without the use of shim volume on Steady State Free Precession (SSFP) sequences so that it can determine the most optimum 4 chamber images to maintain the diagnostic value by physician. Method: This research is designed through quantitative analytic approach with experiment method. The total samples used are 13 subjects ranging from 7 to 80 years old and 5 respondents and the sample undergone into a series of examinations of Cardiac Magnetic Resonance Imaging. Afterward, the 4 chamber sections in SSFP sequence were given different treatment, namely, with and without the use of shim volume. The result will be assessed by the respondents and then it will be done by non-parametric Wilcoxon Two-Sample Test and parametric Paired Sample T Test. Result: Thereafter, the result of statistic from the respondent assessment is that the quality of anatomy images has p=(0.113) whereas the p=(0.354) for the degree of artefact images and clarifies that the anatomy image quality and the degree of artefact is not too much different. Conclusion: The conclusion of the research is with and without the use of shim volume is not too significant to affect the quality of 4 chamber images.